Type 2 diabetes and 10-year risk of dementia and cognitive impairment among older Mexican Americans - Mayeda, Elizabeth R; Haan, Mary N; Kanaya, Alka M; Yaffe, Kristine; Neuhaus, John (Diabetes care, 2013)
Type 2 diabetes has been linked with increased risk of dementia and cognitive impairment among older adults and with premature mortality in young and middle-aged adults. No studies have evaluated the association between diabetes and dementia among Mexican Americans, a population with a high burden of diabetes. We evaluated the association of diabetes with incidence of dementia and cognitive impairment without dementia (CIND) among older Mexican Americans while accounting for competing risk from death. This study included 1,617 participants 60-98 years of age from the Sacramento Area Latino Study on Aging followed up to 10 years from 1998. We evaluated the association between diabetes and dementia/CIND with competing risk regression models. Participants free of dementia/CIND at baseline (n = 1,617) were followed annually up to 10 years. There were 677 (41.9%) participants with diabetes, 159 (9.8%) incident dementia/CIND cases, and 361 (22.3%) deaths. Treated and untreated diabetes (hazard ratio 2.12 [95% CI 1.65-2.73] and 2.15 [1.58-2.95]) and dementia/CIND (2.48 [1.75-3.51]) were associated with an increased risk of death. In models adjusted for competing risk of death, those with treated and untreated diabetes had an increased risk of dementia/CIND (2.05 [1.41-2.97] and 1.55 [0.93-2.58]) compared with those without diabetes. These findings provide evidence that the association between type 2 diabetes and dementia/CIND among Mexican Americans remains strong after accounting for competing risk of mortality. Treatments that modify risk of death among those with diabetes may change future dementia risk.